How do attitudes toward Covid-19 vaccine impact intentions to vaccinate in an emerging economy? The moderating effect of risk perception and Covid-19 anxiety. Issue 4 (2nd October 2021) - Mohanty, Abhijit; Dash, Pranati; Banerji, Diptiman
Abstract: This article aims to investigate the factors influencing the relationship between attitudes toward Covid-19 vaccines and intention to vaccinate, specifically, risk perception and Covid-19 anxiety. The study's results clearly demonstrate that only when the risk perception is minimal does vaccination intention improve with improved vaccine attitudes. The findings of this study provide valuable insights for policymakers, non-government organizations, marketers, and practitioners about the possible challenges in the execution of a Covid-19 vaccination program in an emerging economy. There is a need for tailored communication, community engagement and strictly following the standard operating procedure (SOP) inside the vaccination centers.